When are primary care physicians untruthful with patients? A qualitative study. Issue 1 (2nd January 2017) - Morain, Stephanie R.; Iezzoni, Lisa I.; Mello, Michelle M.; Park, Elyse R.; Metlay, Joshua P.; Horner, Gabrielle; Campbell, Eric G.
ABSTRACT: Background : Notwithstanding near-universal agreement on the theoretical importance of truthfulness, empirical research has documented gaps between ethical norms and physician behaviors. Although prior research has explored situations in which physicians may not be truthful with patients, it has focused on contexts within specialty practice. In this article, we report on a qualitative study of truthfulness in primary care. Methods : We conducted a qualitative study during December 2014–March 2015 involving both focus groups and in-depth, semistructured interviews with 32 primary care physicians from the Boston, MA, and Baltimore, MD, metro areas in three specialties: internal medicine, family practice, and pediatrics. Interviews and focus groups were led using a semistructured guide, which explored situations in which primary care physicians find it difficult to be honest with patients; factors shaping truthfulness; and rationales for truthful and untruthful communication. Results : While physicians described outright lying to patients as rare, other deviations from truthfulness were not uncommon, including slanting and deliberately withholding information. Physicians described a range of factors as influencing truthfulness, from patient-level characteristics such as educational background to societal considerations including avoiding unnecessary tests and procedures. Physicians described truthfulness as an ethical requirement, deviations from which required further justification. Perceived justifications included promoting patient well-being and avoiding harm. Conclusions : Our results suggest a potential need to augment opportunities for training in "everyday ethics" challenges, such as the appropriateness of deception in response to patient requests for inappropriate tests or pain medications. Furthermore, they indicate that, in various circumstances encountered in primary care, physicians perceive other moral duties as potentially in conflict with the duty of truthfulness. Further ethical analysis should focus on identifying when deviations from complete truthfulness do and do not serve patients' interests, to guide physicians in striking a reasonable balance among principles of medical ethics that may conflict with one another.